A new scheme with infusion of hepatitis B immunoglobulin combined with entecavir for prophylaxis of hepatitis B virus recurrence among liver transplant recipients. Issue 8 (August 2015) - Chen, Gang; Liu, Hong; Hu, Zong-Qiang; Bai, Jian-Hua; Liu, Qi-Yu; Zhao, Ying-Peng; Gan, Xue-Mei; Wang, Fan; Wang, Dong-Dong; Ma, Lin-Jie; Li, Li
Abstract : Objective: Liver transplantation significantly increases recurrence of hepatitis B virus (HBV) among high-risk patients. Hepatitis B immunoglobulin (HBIG) and antiviral nucleotide analogues are effective prophylaxis reagents in preventing HBV recurrence. However, HBV recurrence still occurs with these treatments. Methods: To explore a more cost-effective prophylaxis protocol in patients after liver transplantation, we treated patients with an initial high dose of 10 000 IU HBIG during the anhepatic phase and a second high dose of HBIG at an optimal time point during surgery. The patients were treated with the traditional European protocol as a control, in which one dose of 10 000 IU HBIG was infused during the anhepatic phase and multiple doses of 10 000 IU HBIG were administered daily for 1 week after liver transplantation. Results: There were two mortalities among 50 patients treated with the new protocol and nine mortalities among 52 patients treated with the European protocol within 3 years after liver transplantation. The new prophylaxis method markedly improved the 3-year survival without HBV recurrence in 50 treated patients. However, there were five recurrences in 52 patients treated with the European protocol. High-risk factors such as HBV DNA+, positive hepatitis B e antigen, and hepatocellular carcinoma were all detected among five patients with HBV recurrence. The suppressed HBV recurrence was associated with significantly lower serum alanine aminotransferase and aspartate aminotransferase in the new protocol-treated patients tested at 1 month and 1 week after liver surgery compared with those treated with the European protocol. Conclusion: Infusion of two high doses of HBIG during surgery in combination with entecavir significantly prevented HBV recurrence and improved the 3-year survival after liver transplantation.